The fight against taro blight - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
For Samoa, taro was a major export crop and national staple food until the crop was wiped out by taro leaf blight in 1993. Scientists at the University of the South Pacific (USP), Western Samoa, are currently trying to overcome the regional problem...